2013
DOI: 10.1111/bcpt.12105
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor Dysfunction in the Mesenteric Artery after Organ Culture with Cyclosporin A

Abstract: Cyclosporin A (CsA) is a widely used immunosuppressive agent that also causes hypertension. However, the molecular basis for CsA-induced hypertension remains elusive. In this study, we established an in vitro model for CsA-induced pathological changes in vasculature. Rat mesenteric arteries were incubated with CsA for 24 hr in an organ culture system. Both vasocontraction and vasorelaxation in mesenteric artery were studied using myograph technology, and mRNA expressions of the contractile receptors were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Our previous study showed the ET B -mediated vasoconstriction was enhanced after organ culture with CsA in a dose-dependent manner (Zheng et al, 2013). The present data showed mRNA expression of ET B receptor was augmented by CsA treatment in the dose-and time-dependent manner (Fig.…”
Section: The Effect Of Csa On Et B Receptor Mrna and Protein Expressionsupporting
confidence: 68%
See 4 more Smart Citations
“…Our previous study showed the ET B -mediated vasoconstriction was enhanced after organ culture with CsA in a dose-dependent manner (Zheng et al, 2013). The present data showed mRNA expression of ET B receptor was augmented by CsA treatment in the dose-and time-dependent manner (Fig.…”
Section: The Effect Of Csa On Et B Receptor Mrna and Protein Expressionsupporting
confidence: 68%
“…1) and protein expression (Fig. 2), and ET B receptor-mediated vasoconstriction (Zheng et al, 2013); and these changes were attenuated by transcription inhibitor AcD (Figs. 3 and 4), suggesting the de novo transcriptional mechanism contributed to upregulation of ET B receptor induced by CsA.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations